1991
DOI: 10.1210/endo-129-3-1167
|View full text |Cite
|
Sign up to set email alerts
|

Direct and Sex-Specific Enhancement of Bone Formation and Calcification by Sex Steroids in Fetal Mice Long Bonein Vitro(Biochemical and Morphometric Study)*

Abstract: The study was carried out to examine the direct effect of the sex hormones 17 beta-estradiol (E2) and testosterone on the modeling of cultured fetal mouse long bones separated according to their sex. The culture system used allowed for the simultaneous assessment of bone growth, mineralization, and resorption on each bone. Bones from 16-day-old male and female mouse fetuses were cultured in BGJ medium, supplemented with either 10% fetal calf serum or 4 mg/ml BSA (serum-free medium) for 48 h. The bones were har… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
4
1

Citation Types

1
15
0
1

Year Published

1998
1998
2009
2009

Publication Types

Select...
8

Relationship

1
7

Authors

Journals

citations
Cited by 55 publications
(17 citation statements)
references
References 0 publications
1
15
0
1
Order By: Relevance
“…In line with our findings, AR stimulation was previously demonstrated not to affect the length of cultured fetal rat metatarsal bones [27]. Nevertheless, androgen responsiveness might differ between species, which is supported by the observations that dihydrotestosterone increases DNA synthesis in fetal human epiphyseal chondrocytes [28], and that testosterone stimulates the growth of mouse cartilage [29, 30]. Nevertheless, in cultured fetal rat metatarsal bones, dihydrotestosterone has been demonstrated to prevent the negative effects of glucocorticoids [27], raising the possibility that rat cartilage might be androgen-responsive anyway.…”
Section: Discussionsupporting
confidence: 90%
See 1 more Smart Citation
“…In line with our findings, AR stimulation was previously demonstrated not to affect the length of cultured fetal rat metatarsal bones [27]. Nevertheless, androgen responsiveness might differ between species, which is supported by the observations that dihydrotestosterone increases DNA synthesis in fetal human epiphyseal chondrocytes [28], and that testosterone stimulates the growth of mouse cartilage [29, 30]. Nevertheless, in cultured fetal rat metatarsal bones, dihydrotestosterone has been demonstrated to prevent the negative effects of glucocorticoids [27], raising the possibility that rat cartilage might be androgen-responsive anyway.…”
Section: Discussionsupporting
confidence: 90%
“…This is supported by our recent demonstration that aromatase is indeed expressed in fetal rat metatarsal bones, and that endogenously produced estrogens are capable of stimulating chondrocyte proliferation and fetal rat metatarsal bone growth [18]. Interestingly, it has previously been shown that testosterone is capable of stimulating growth of fetal mouse metatarsal bones only when cultured in the presence of serum [29]. This finding, together with our present observation that oxandrolone does not affect bone growth in the presence of serum, suggest that aromatization of testosterone occurs within the growth plate.…”
Section: Discussionmentioning
confidence: 64%
“…This is in agreement with the findings of most previous immunohistochemical studies in human (Abu et al 1997, Kusec et al 1998, Bord et al 2001, rat (van der Eerden et al 2002a and rabbit (Kusec et al 1998 growth plate cartilage. Thus the sex-specific effects of sex steroids suggested by the findings of some in vitro studies (Corvol et al 1987, Blanchard et al 1991, Schwartz et al 1991, do not appear to be caused by sex-specific receptor expression. However, immunohistochemistry is a semi-quantitative method, and real differences could have been overlooked by this technique.…”
Section: Discussionmentioning
confidence: 87%
“…Several in vitro and in situ studies have suggested that the sex steroid responsiveness of growth plate cartilage is dependent on the sex (Carrascosa et al 1990, Schwartz et al 1991, Nasatzky et al 1993, van der Eerden et al 2002b or the age, or both (Corvol et al 1987, Blanchard et al 1991, Pinus et al 1993) of the individual. However, few studies have addressed this issue in human growth plate cartilage.…”
Section: Introductionmentioning
confidence: 99%
“…4): this might partly explain why DHT had no significant direct effect per se on any parameter tested in this experiment. However, Schwartz et al [53] did not demonstrate any effect of testosterone (10 -7 M) on bone resorption measured by 45 Ca release from fetal long bones after 48 h of culture. Furthermore, the therapeutic potential should be tapered by the potential disadvantage of giving testosterone or DHT which have several potential side effects.…”
Section: Discussionmentioning
confidence: 93%